Neuroevolution of convolutional neural networks for the classification of lung cancer images - Радюк, Павло Михайлович; Radiuk, Pavlo M. (My University, 2018)
Convolutional neural networks demonstrate impressive results during medical imaging of lung cancer. It may be possible to make diagnoses with convolutional neural networks on conventional chest X-rays that are definitively apparent on subsequently computed tomography and biopsy. Computer vision may reduce the need for further evaluation with invasive testing or prevent errors of missed diagnoses. Using over twelve thousand images of proven lung cancer from the Prostate, Lung, Colorectal, and Ovarian dataset, we developed an algorithm to predict the presence or absence of lung cancer. The classification algorithm has achieved an accuracy of 96.09% with a positive predictive value of 99.11% and a negative predictive value of 93.25%.

Згорткові нейронні мережі демонструють вражаючі результати під час медичної візуалізації раку легенів. Є можливість провести діагнози з використанням згорткових нейронних мереж за звичайними рентгенівськими знімками грудної клітки, які остаточно проявляються на подальшій комп'ютерній томографії та біопсії. Комп'ютерне бачення може зменшити потребу в подальшій оцінці за допомогою інвазивного тестування або запобігання помилкам пропущених діагнозів. Використовуючи понад дванадцять тисяч зображень виявленого раку легень із набору даних з раком простати, легень, колоректалу та яєчників, ми представляємо алгоритм для прогнозування наявності або відсутності раку легенів. Алгоритм класифікації досягнув точності розпізнавання 96.09% з позитивною прогностичною цінністю 99.11% та негативною прогностичною цінністю 93.25%
Radiuk P. M. Neuroevolution of convolutional neural networks for the classification of lung cancer images / P. M. Radiuk //Вісник Хмельницького національного університету. – Том 2. – №6. – 2018 (267). – С. 188-192. DOI 10.31891/2307-5732-2018-267-6(2)-188-192
Keywords: convolutional neural networks; genetic algorithms; hyperparameters; dataset; lung cancer; згорткові нейронні мережі; генетичні алгоритми; гіперпараметри; набір даних; рак легень; Research Subject Categories::TECHNOLOGY; Research Subject Categories::MEDICINE